Developing a project within a school-university partnership: factors that influence effective partnership working. Issue 2 (4th March 2021) - Marsh, Brian
ABSTRACT: This paper advances the discourse on school-university partnerships by considering the challenges of implementing a project to support the professional development of teachers through the use of video-mediated lesson observation within such a partnership network. The project discussed here was initially established by teacher-educators and located in the secondary sector of a school-university partnership in England. It offers an interpretive framework for analysing school-university partnerships. The impact of this project was limited due to asymmetric power relations. The effectiveness of partnership working is discussed by considering the degree of congruence between the perspectives of and division of labour between both school-based mentors and teacher-educators and those factors identified in literature as supporting effective partnership working. The findings point to effectiveness being compromised when power and control are located within one community resulting in school-based mentor disengagement and the project aims only being partly fulfilled.